Predictors of consistent condom use based on the Information-Motivation-Behavioral Skills (IMB) model among female sex workers in Jinan, China - Tao Xiaorun; Zhang Changqing; Ruan Shiman; Wang Chuangxin; Pan Rongjian; Nie Xijuan; Liao Meizhen; Zhang Hua; Kang Dianmin; Jiang Baofa (BMC, 2011)
Abstract Background Female commercial sex workers (FSWs) are at high risk of human immunodeficiency virus (HIV) transmission in China. This study was designed to examine the predictors of condom use with clients during vaginal intercourse among FSWs based on the Information-Motivation-Behavioral Skills (IMB) model and to describe the relationships between IMB model constructs. Methods A cross-sectional study was conducted in Jinan of Shandong Province, from May to October, 2009. Participants (N = 432) were recruited using Respondent-Driven Sampling (RDS). A self-administered questionnaire was used to collect data. Structural equation modeling was used to assess the IMB model. Results A total of 427 (98.8%) participants completed their questionnaires. Condom use was significantly predicted by social referents support, experiences with and attitudes toward condoms, self-efficacy, and health behaviors and condom use skills. Significant indirect predictors of condom use mediated through behavioral skills included HIV knowledge, social referents support, and substance use. Conclusions These results suggest that the IMB model could be used to predict condom use among Chinese FSWs. Further research is warranted to develop preventive interventions on the basis of the IMB model to promote condom use among FSWs in China.